Antidepressant-like Effects of Combined Fluoxetine and Zinc Treatment in Mice Exposed to Chronic Restraint Stress Are Related to Modulation of Histone Deacetylase - Misztak, Paulina; Sowa-Kućma, Magdalena; Pańczyszyn-Trzewik, Patrycja; Szewczyk, Bernadeta; Nowak, Gabriel (Molecules (Basel, Switzerland), 2021)
Chronic stress is the key factor contributing to the development of depressive symptoms. Chronic restraint stress (CRS) is well validated and is one of the most commonly used models to induce depressive-like behavior in rodents. The present study aimed to evaluate whether fluoxetine (FLU 5 mg/kg) and zinc (Zn 10mg/kg) given simultaneously induce a more pronounced antidepressant-like effect in the CRS model than both those compounds given alone. Behavioral assessment was performed using the tail suspension and splash tests (TST and ST, respectively). Furthermore, the effects of CRS, FLU and Zn given alone and combined treatment with FLU + Zn on the expression of proteins involved in the apoptotic, inflammatory, and epigenetic processes were evaluated in selected brain structures (prefrontal cortex, PFC; and hippocampus, Hp) using Western blot analysis or enzyme-linked immunosorbent assays (ELISA). The results obtained indicated that three hours (per day) of immobilization for 4 weeks induced prominent depressive symptoms that manifested as increased immobility time in the TST, as well as decreased number and grooming time in the ST. Behavioral changes induced by CRS were reversed by both FLU (5 and 10 mg/kg) or Zn (10 mg/kg). Zinc supplementation (10 mg/kg) slightly increases the effectiveness of FLU (5 mg/kg) in the TST. However, it significantly increased the activity of FLU in the ST compared to the effect induced by FLU and Zn alone. Biochemical studies revealed that neither CRS nor FLU and Zn given alone or in combined treatment alter the expression of proteins involved in apoptotic or inflammatory processes. CRS induced major alterations in histone deacetylase (HDAC) levels by increasing the level of HADC1 and decreasing the level of HADC4 in the PFC and Hp, decreasing the level of HADC6 in the PFC but increasing it in Hp. Interestingly, FLU + Zn treatment reversed CRS-induced changes in HDAC levels in the Hp, indicating that HDAC modulation is linked to FLU + Zn treatment and this effect is structure-specific.